The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/2249-4863.214983
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment among 10–14-year school children in Puducherry: A cross-sectional study

Abstract: Introduction:According to the 2010 estimates by the World Health Organization, nearly 285 million (4.24% of total population) people of all ages worldwide are visually impaired. Almost 18.9 million children under 15 years of age are visually impaired globally. In developing countries, 7%–31% of childhood blindness and visual impairment is avoidable.Materials and Methods:The study was conducted as a cross-sectional study among 1884 school students in Puducherry, in the age group of 10–14 years. A child with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
(9 reference statements)
2
10
3
Order By: Relevance
“…However, the prevalence in the study area was lower than other study reports of developed countries such as Egypt (29.4%) [27], Northern Ireland (3.6%) [21], Nepal (9.1%) [22], Brazil (2.67% and 4.82%) [28,29], two regions of China (6.37% and 7.7%) [30,31], and Australia (6.4%) [32]. is is probably due to variation in the measurement of visual impairment, where in this study, children presenting with a visual acuity of <6/18 in the better eye were considered as visually impaired, whereas majority of the above used children presenting with a visual acuity of less than or equal to 6/12 and specifically, vision ≤6/9 was used in Egypt.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the prevalence in the study area was lower than other study reports of developed countries such as Egypt (29.4%) [27], Northern Ireland (3.6%) [21], Nepal (9.1%) [22], Brazil (2.67% and 4.82%) [28,29], two regions of China (6.37% and 7.7%) [30,31], and Australia (6.4%) [32]. is is probably due to variation in the measurement of visual impairment, where in this study, children presenting with a visual acuity of <6/18 in the better eye were considered as visually impaired, whereas majority of the above used children presenting with a visual acuity of less than or equal to 6/12 and specifically, vision ≤6/9 was used in Egypt.…”
Section: Discussioncontrasting
confidence: 60%
“…This finding was comparable with a study conducted in India reporting that males were also more affected by visual impairment at 31.60% than females at 22.20%. 12 The use of eye care services could be unequal between males and females at this stage and it can be a subject for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Second, vision disability rates among girls living in rural versus urban areas within the MDR were not significantly different. The findings of this study are not in agreement with the findings of other studies, which have shown that vision impairment is more prevalent in urban areas, in part due to differences in lifestyle (eg, more frequent participation in indoor leisure activities, such as watching television or using a computer) …”
Section: Discussionmentioning
confidence: 99%